Do Improving Conditions Harden Partisan Preferences? Lived Experiences, Imagined Communities, and Polarized Evaluations. (23rd January 2020) - Suk, Jiyoun; Shah, Dhavan V; Wells, Chris; Wagner, Michael W; Friedland, Lewis A; Cramer, Katherine J; Hughes, Ceri; Franklin, Charles
Abstract: Despite growing attention to an increasing partisan divide and populist voting, little attention has been directed at how social contexts might encourage greater or lesser political polarization. We address this gap by studying how county-level conditions—economic resilience, population change, and community health—intersect with individuals' political orientations and communication patterns to shape partisan evaluations. Our context is Wisconsin around the 2012 election, with our focus on two prominent political figures: Governor Scott Walker and President Barack Obama. Multilevel modeling reveals that partisans living in counties with more affluent, less precarious conditions during 2009–2012 exhibited more polarized partisan attitudes toward Walker and Obama. Our analysis also finds a significant role for interpersonal communication and digital media in shaping polarized attitudes.